(untitled) (Revista educación, investigación, innovación y transferencia, 2025)
This paper examines a bilingual telecollaboration project between undergraduate students at the University of Technology Sydney (UTS), Australia, and the Universidad de Zaragoza, Spain. The study adds to the growing body of research on virtual linguistic and cultural exchanges by describing and evaluating this bilingual Spanish-English initiative through the analysis of the students’ perceptions especially as regards their development of communication skills, Intercultural Communicative Competences (ICC) and global citizenship skills. It further aims to enhance our understanding of intercultural learning through telecollaborations that provide a scalable model for expanding students’ linguistic and intercultural exposure through technology (Byram, 1997; Ryshina-Pankova, 2018). The primary objectives of the telecollaboration initiative were to support students’ development of (i) ICC by preparing them in their second language (L2)—English for the Spanish students and Spanish for the Australian students—through engagement with cultural differences between Spain and Australia, and (ii) oral skills in their L2, particularly in their use of interactional strategies. Findings from the completion of the exchanges and the students’ answers to the questionnaire administered indicate that both English-speaking Australian and Spanish-speaking students engaged in meaningful intercultural communication, demonstrating negotiation and reflection skills despite limited L2 proficiency. The bilingual telecollaborative experience seems to effectively enhance students’ oral skills and intercultural awareness, fostering their capacity to participate actively and critically in global communities.